Challenges to Globalisation in the Age of Artificial Intelligence. Global Risks and Global Network Platforms. Global Citizenship - Panayotova, Monika (Research Papers, 2025)
This study aims to present key challenges to globalisation in the era of artificial intelligence (AI), focusing the attention on contemporary multifaceted global risks, global social networks and platforms, and the importance of global citizenship in addressing them. Specific emphasis is placed on emerging global technological challenges related to: disinformation and the vulnerability of democratic societies and systems; the growing fight for cognitive superiority; the adverse outcomes of AI technologies; and global network platforms gaining increasing geopolitical weight due to their possession and trade in the ’oil’ of the digital age called – data.The publication demonstrates the importance of education in overcoming these challenges through global citizenship, media literacy, social and cognitive skills development.Revealing the possible prospects for de-globalisation and re-globalisation in the age of artificial intelligence, the study notes that the chances of digital connectivity, a positive effect of the application of AI and the emergence of a “sixth freedom” in EU associated with the free movement of data, are greater, if the still-dominant democratic powers of the world act proactively, they can mitigate the risks posed by de-globalisation, through multilateral cooperation, building a sound regulatory basis for digital connectivity and education for digital citizenship.For the purpose of the publication, the survey method was used by presenting results from author’s questionnaire, as well as the methods of analysis and synthesis of primary and secondary sources of information, generalisation, inductive and deductive research approaches.